The Effect of A Combination of Hydrotherapy Drinking Water and Acupressure on the KGDS of DM Patients - Evi Martalinda Harefa; Cipta Citra Karyani Gulo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia resulting from abnormalities in insulin secretion, insulin action, or both. Diabetes Mellitus remains a significant health problem and a priority target for global follow-up due to its dangerous impacts and increasing prevalence annually. Complementary therapy, a combination of hydrotherapy, drinking water, and acupressure, is a non-pharmacological therapy that can be administered to control blood sugar levels in diabetes mellitus patients. This combination of therapies has been proven to be more effective in controlling blood glucose levels in diabetes mellitus patients because it can impact the excretion of excess sugar in the body while simultaneously affecting the hypothalamus by activating one of the carbohydrate metabolism enzymes (glucose-6-phosphate). In the pancreas, it increases insulin synthesis, increases receptors on target cells, and accelerates glucose utilization in cells. The purpose of this study was to analyze the effect of the combination of drinking water hydrotherapy and acupressure therapy on blood glucose levels during Type II DM patients in Ilir Village, Gunungsitoli District Health Center Working Area in 2024. This type of research is quasi-experimental with a nonequivalent control group design approach. The study population was all Type 2 DM patients in Ilir Village, Gunungsitoli District Health Center Working Area with a sample size of 32 respondents. The sampling technique was purposive sampling. The sample was selected according to the researcher's wishes with inclusion criteria: age 30-70 years, type 2 diabetes mellitus diagnosed by a doctor, stable drug therapy ≥ 4 weeks (no change in dose/type of insulin), random blood sugar 140-300 mg/dl, good hydration status, adequate kidney function and no fluid restrictions, controlled blood pressure; exclusion criteria: type 1 DM, gestational DM, changes in antihyperglycemic therapy < the last 4 weeks, suffering from kidney failure, heart failure, experiencing acute infections, uncontrolled blood pressure, skin disorders/wounds. Researchers used repeated ANOVA tests if the data were normally distributed or Friedman Tests if the data were not normally distributed. For comparison of the intervention and control groups, researchers used t-tests if they were normally distributed or Mann Whitney if they were not normally distributed. From the results of the repeated ANOVA test, it was known that the Greenhouse-Geisser significance value was 0.001 (p = <0.05), which means there was a significant difference between blood sugar levels before and after the intervention in the intervention group. From the results of the independent t-test, it is known that the two-sided significant value is 0.001 (p < 0.05), which means there is a significant difference between random blood sugar levels in the intervention group and the control group after intervention 3. The conclusion of this study is that the combination of drinking water hydrotherapy and acupressure has an effect on the KGDS of diabetes mellitus patients.